(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
Using A. Missenard’s normal equivalent-effective temperature formula, warm season weather conditions’ comfort of Syunik Region is defined in the article. Comfort time duration is defined based on Isaev’s approach. The latter is different in different landscape zones, so we considered it necessary to do our research by landscapes zones. The analysis was carried out on an annual basis. As it is not enough, it was decided to carry analysis of obtained data also on monthly basis, and that fully proves the situation in the region. Оbtained data is analyzed and evaluated as it needed and grouped into three groups by level of auspiciousness. Territories with 12–15℃ value of equivalent-effective temperature are considered as poor comfort territories, territories with 15–20℃ value of temperature are comfort, and territories with more than 20℃ value of temperature are discomfort territories. Analysis proved that the montane forests zone is characterized with the long duration of comfort days, where the 76.7% of warm season is considered as comfort. In dry steppe zone 73% of warm season is comfort. With the less duration of comfort days is characterized the mountain-meadow zone, where only 23.3% of warm season days are comfort. Results of this article can be used for choosing favorable territories for recreation and human health improvement. Based on monthly basis research results and through a migration it is possible to choose a living place for people with dependence on meteorological conditions.